2017
DOI: 10.1128/mbio.00211-17
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Heparan Sulfate Linked to Neutrophil Dysfunction in the Acute Inflammatory Response Associated with Experimental Vulvovaginal Candidiasis

Abstract: Despite acute inflammation by polymorphonuclear neutrophils (PMNs) during vulvovaginal candidiasis (VVC), clearance of Candida fails to occur. The purpose of this study was to uncover the mechanism of vaginal PMN dysfunction. Designs included assessing PMN migration, proinflammatory mediators, and tissue damage (by analysis of the activity of lactate dehydrogenase [LDH]) in mice susceptible (C3H/HeN-C57BL/6) or resistant (CD-1) to chronic VVC (CVVC-S or CVVC-R) and testing morphology-specific Candida albicans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
58
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 55 publications
13
58
2
1
Order By: Relevance
“…Although in the current study we could not detect a correlation between IgG titers of NR and R vaccinated subjects and their corresponding IFN- levels, antisera from NR patients significantly enhanced the ability of human neutrophils to kill C. albicans ex vivo as compared to antisera from R patients or patients administered placebo. These results are concordant with the finding that RVVC is a disease in which a discordance of exacerbated neutrophil influx often occurs in the face of inefficiency in clearing the infection (3234). We postulate that in NR women, the vaccine was able to induce an antibody response that; 1) protected against C. albicans adherence to and invasion of mucocutaneous barriers; 2) reduced the capability of the organism to form biofilm from which persistent infection occurs; 3) induced a coordinated phagocyte response that is more efficacious in clearing the infection; and/or 4) modulated profusive inflammatory responses of the host associated with relapse.…”
Section: Discussionsupporting
confidence: 90%
“…Although in the current study we could not detect a correlation between IgG titers of NR and R vaccinated subjects and their corresponding IFN- levels, antisera from NR patients significantly enhanced the ability of human neutrophils to kill C. albicans ex vivo as compared to antisera from R patients or patients administered placebo. These results are concordant with the finding that RVVC is a disease in which a discordance of exacerbated neutrophil influx often occurs in the face of inefficiency in clearing the infection (3234). We postulate that in NR women, the vaccine was able to induce an antibody response that; 1) protected against C. albicans adherence to and invasion of mucocutaneous barriers; 2) reduced the capability of the organism to form biofilm from which persistent infection occurs; 3) induced a coordinated phagocyte response that is more efficacious in clearing the infection; and/or 4) modulated profusive inflammatory responses of the host associated with relapse.…”
Section: Discussionsupporting
confidence: 90%
“…Fidel and colleagues presented a novel hypothesis referred to as "neutrophil anergy" to help explain neutrophil inactivity in the vagina [105]. C57BL/6 mice are highly susceptible to estrogen-dependent VVC, while CD-1 mice are relatively resistant to vaginal colonization [106,107]. Interestingly, supplementation of cell culture medium with vaginal fluid obtained from C57BL/6 mice significantly impeded neutrophil-mediated killing of C. albicans in vitro, while fluid from CD-1 mice was similar to untreated control medium.…”
Section: Estrogen-dependent Immunomodulationmentioning
confidence: 99%
“…The active compound in C57BL/6 fluid was identified as heparan sulfate, and its effects on PMN activity could be mitigated by degradation with heparanase. Evidently, heparan sulfate is a competitive inhibitor of Mac1, present on neutrophils and interferes with recognition of the fungal surface ligand Pra1p, allowing C. albicans to evade killing [107]. Given that heparan sulfate is estrogen-inducible, this could provide a rationale as to why neutrophils are ineffective at clearing C. albicans in vivo.…”
Section: Estrogen-dependent Immunomodulationmentioning
confidence: 99%
“…Indeed, recent work by Yano et al demonstrated that heparin sulfate can be recovered from the vaginal lavage fluid of mice and that its presence is enhanced by exogenous estrogen administration (29). Interestingly, treatment of recovered vaginal fluid with heparinase restored the capacity of PMNs to kill C. albicans in vitro, suggesting that heparin sulfate may phenotypically alter or physically inhibit neutrophil-fungus interaction.…”
Section: Figmentioning
confidence: 99%
“…Interestingly, treatment of recovered vaginal fluid with heparinase restored the capacity of PMNs to kill C. albicans in vitro, suggesting that heparin sulfate may phenotypically alter or physically inhibit neutrophil-fungus interaction. One potential mechanism was presented whereby heparin sulfate outcompetes the fungal surface antigen Pra1 for its natural ligand Mac1, present on the surfaces of neutrophils to prevent killing of the fungus (29,30). Although the precise role of heparin sulfate at the vaginal mucosa remains unclear, it is often upregulated in other epithelial or epidermal tissues in response to damage, functioning in the tissue repair process (31).…”
Section: Figmentioning
confidence: 99%